Direct Neck Lift in Men - Velargo, Parker A.; Holtrop, John C.; Aukerman, Bill D.; Sohini, Vidhur R. (Facial Plastic Surgery, 2025)
Direct submentoplasty remains a valuable alternative to rhytidectomy in male patients, addressing cervical laxity and fullness while avoiding feminization, periauricular scars, and prolonged recovery associated with traditional rhytidectomy.Since the early 20th century, submental skin excision has undergone refinement, progressing from horizontal ellipses to advanced configurations such as the Grecian urn pattern. These modifications aim to optimize scar camouflage while correcting horizontal and vertical redundancy.Key anatomic contributors to cervical aging include skin and platysmal laxity, supra- and subplatysmal fat, anterior belly of the digastric hypertrophy, ptotic submandibular glands, and a low-lying hyoid. Comprehensive preoperative analysis is required to address these factors.For patients presenting with submental fullness accompanied by good skin elasticity and minimal skin laxity, an isolated deep structural neck lift without skin excision may be sufficient. Optimal candidates for direct cervicoplasty (skin excision) demonstrate submental laxity limited to above the thyroid cartilage, minimal jowling, and acceptance of an anterior cervical scar.The isolated deep structural neck lift addresses the platysma and its underlying structures without the need for skin excision. A direct cervicoplasty with skin excision affords wide exposure for addressing the skin, platysma, and the subplatysmal anatomy. Skin excision patterns are varied and tailored to the patient's needs.Scar modulation strategies, drain management, lymphatic assistance with positioning/massage, and salivary flow management are key to a hastened recovery.Direct submentoplasty remains an essential tool in the aging male patient, offering reproducible results in appropriately selected patients who are willing to accept its limitations.
Keywords: direct neck lift; neck lift; deep neck lift; male neck lift; direct cervicoplasty